2020
DOI: 10.3390/jof6030104
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity Levels of Colombian Strains of Candida auris and Brazilian Strains of Candida haemulonii Species Complex in Both Murine and Galleria mellonella Experimental Models

Abstract: Candida auris and Candida haemulonii complex (C. haemulonii, C. haemulonii var. vulnera and C. duobushaemulonii) are phylogenetically related species that share some physiological features and habits. In the present study, we compared the virulence of these yeast species using two different experimental models: (i) Galleria mellonella larvae to evaluate the survival rate, fungal burden, histopathology and phagocytosis index and (ii) BALB/c mice to evaluate the survival. In addition, the fungal capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 39 publications
5
39
0
Order By: Relevance
“…These results are consistent with those reported by Borman et al (2016) [ 21 ] who first described the formation of aggregates by some C. auris isolates, which later was corroborated by Sherry et al (2017) [ 22 ] and Muñoz et al (2020) [ 11 ]. These studies reported that C. auris did not form hyphae unlike C. albicans in the G. mellonella model of candidiasis, and that non-aggregating C. auris isolates were more virulent, even when compared to some C. albicans isolates [ 11 , 21 , 22 ]. In a murine model, Ben-Ami et al (2017) [ 13 ] also identified yeast cells during the infection and recovered aggregates from murine tissues.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…These results are consistent with those reported by Borman et al (2016) [ 21 ] who first described the formation of aggregates by some C. auris isolates, which later was corroborated by Sherry et al (2017) [ 22 ] and Muñoz et al (2020) [ 11 ]. These studies reported that C. auris did not form hyphae unlike C. albicans in the G. mellonella model of candidiasis, and that non-aggregating C. auris isolates were more virulent, even when compared to some C. albicans isolates [ 11 , 21 , 22 ]. In a murine model, Ben-Ami et al (2017) [ 13 ] also identified yeast cells during the infection and recovered aggregates from murine tissues.…”
Section: Resultssupporting
confidence: 92%
“…These results are comparable to those obtained in other studies, which observed that C. auris caused death of G. mellonella within 48 h [ 21 , 22 ] and of C. elegans between 48 and 96 h post-infection [ 23 , 29 ]. Our findings corroborate the idea that both models successfully demonstrate the virulence potential of C. auris , which was similar to or higher than that of other Candida species [ 11 , 30 , 32 , 33 , 52 ]. The observed virulence of C. auris was comparable to C. albicans [ 21 , 22 , 29 ] and higher than isolates from C. haemulonii complex species [ 11 , 29 ].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…For this reason, different models that are easier to use have recently been chosen, and one of them is the invertebrate Galleria mellonella . In recent years, this experimental model has been crucial for understanding the pathogenicity of different Candida species, and relatively inexpensive compared to the murine model [ 16 , 17 ]. The advantage of using G. mellonella as a model for the study of pathogenicity in fungi is the ease of use, that is, the inoculation of the pathogen involves only a hind leg and a syringe, and they can be maintained at variable temperatures ranging from 25 to 37 °C.…”
Section: Introductionmentioning
confidence: 99%